Islam and Women's Emancipation: Initiating Progressive Steps Towards Muslim Gender Equality in Indonesia - Firmansyah, Rezky (Journal of Feminism and Gender Studies, 2024)
This article explores the intersection of Islam and women's emancipation in Indonesia, focusing on progressive steps towards gender equality. Drawing from Islamic principles advocating for equal rights and opportunities for both genders, the article examines concrete measures for achieving gender equality within the Muslim community in Indonesia. It delves into the importance of inclusive education, economic empowerment, legal protection, advocacy, and women's involvement in decision-making processes. By elucidating the conceptual framework and discussing practical strategies, the article aims to contribute to ongoing efforts in promoting gender equality within the Indonesian Muslim society.